Erythema Multiforme Induced by a “Milker’s Nodule” Pseudocowpox Infection: A Case Report and Review of Literature - Kyle Wu; Sara de Menezes; Aaron Robinson (Case Reports in Dermatological Medicine)
Milker’s nodule is caused by the pseudocowpox virus following inoculation from infected cattle. We report the case of erythema multiforme induced by pseudocowpox infection in an 18-year-old female from regional Australia. While erythema multiforme has been described as a complication of orf, it is rare as a sequela of pseudocowpox infection. Greater clinical knowledge of this disease and potential complications aid in guiding appropriate management of this phenomenon.